Alternative proposal for including a risk-equalizing criterion in the computation of the power dispatch for the colombian electricity market (2006)
In Colombia, the calculation of the generation office is carried out in four stages. In each of them safety and reliability restrictions are added. One of the most important features of dispatch calculation is the inclusion of a risk equalization policy. The dispatch must be such that the expected relative rations in each of the sub-areas of the system are minimal and close to the arithmetic average. This article presents a linear optimization model that allows the generation dispatch to be calculated in a single stage and that includes this risk equalization policy.